THE EFFECTIVENESS OF THE SIMKAH APPLICATION IN MARRIAGE REGISTRATION ADMINISTRATION AT THE OFFICE OF RELIGIOUS AFFAIRS (KUA) OF BATUMANDI SUB-DISTRICT, BALANGAN REGENCY - M. Husaini; Riswandi Ahdiat; Rahmad Reza Ariadi (PPPM STIA Amuntai, 2025)
The effectiveness of the SIMKAH (Marriage Management Information System) application in managing marriage registration administration at the Office of Religious Affairs (KUA) in Batumandi Subdistrict, Balangan Regency, faces several challenges. These include limited understanding among prospective brides and grooms regarding the existence of this online based registration system, a lack of human resource capacity due to the absence of dedicated personnel to operate the SIMKAH application resulting in the penghulu (marriage officiant) also serving as the operator and technical issues such as server and network disruptions that delay the uploading of required documents. The findings indicate that the use of the SIMKAH application in the marriage registration process at the KUA of Batumandi Subdistrict is less than effective. This is reflected in several indicators. While access, target achievement, and procedures were found to be effective, other indicators such as timeliness, socialization, training, and infrastructure were deemed less effective. Supporting factors include SIMKAH’s integration with the Population Administration Information System (SIAK) managed by the Civil Registry Office (Disdukcapil), and the availability of clear Standard Operating Procedures (SOPs). Inhibiting factors include limited public understanding of the application, insufficient user guidance, and recurring server downtimes. To improve the effectiveness of the SIMKAH application in marriage registration administration, it is recommended that: the Head of KUA address technical infrastructure issues; operators continue to enhance their technical skills; and the public be encouraged to submit required documents within the specified timeframe.